2019
DOI: 10.33151/ajp.16.626
|View full text |Cite
|
Sign up to set email alerts
|

What constitutes an emergency ambulance call?

Abstract: IntroductionAmbulance services are often utilised for low-acuity conditions. This study seeks to understand under what medical circumstances the Australian public perceive it to be appropriate to call triple zero requesting ambulance assistance.Methods A total of 544 participants completed a 15-minute online survey distributed via social media, flyers and email links. Participants viewed 17 medical case study scenarios, developed in consultation with a panel of paramedic experts, and were asked to sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
3
10
3
Order By: Relevance
“…However, this does not imply that SCs are not useful. Specifically, our data confirm a prior study showing that the lay population has difficulties reliably identifying medical emergencies [ 25 ]. On average, participants failed to identify every third emergency, and 12% (11/91) of our participants identified emergencies less reliably than the worst-performing SC.…”
Section: Discussionsupporting
confidence: 88%
“…However, this does not imply that SCs are not useful. Specifically, our data confirm a prior study showing that the lay population has difficulties reliably identifying medical emergencies [ 25 ]. On average, participants failed to identify every third emergency, and 12% (11/91) of our participants identified emergencies less reliably than the worst-performing SC.…”
Section: Discussionsupporting
confidence: 88%
“…As previously reported [ 15 , 23 ], laypersons’ ability to triage is systematically biased toward overtriage, but they tend to miss emergency cases. However, when analyzing actionable metrics of triage ability, we see a majority of laypersons being fairly competent (accuracy ≥75%) in deciding whether they should seek health care (decision 2) and whether emergency care is required (decision 1).…”
Section: Discussionmentioning
confidence: 65%
“…For example, previous studies indicate that laypersons tend to overtriage [ 13 ] and that women rate symptoms as more urgent than men [ 14 ] and are thus potentially even more inclined toward overtriage. Moreover, an Australian study showed that although laypersons are risk averse when making triage decisions, they cannot reliably detect emergencies either [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since there are several factors to consider such as socioeconomic, cultural factors, and patients' personal situations, it is very difficult to analyze the adequacy of EMS system use and establish unified criteria. e use of the EMS system largely depends on a patient's subjective judgment [17][18][19][20]. For this reason, it is hard to set clear criteria for using the system.…”
Section: Discussionmentioning
confidence: 99%